2019
DOI: 10.1111/1753-6405.12937
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to vaccination service delivery within general practice: opportunity to make a sustainable difference in Aboriginal child health?

Abstract: Objective: To identify behavioural barriers of service provision within general practice that may be impacting the vaccination coverage rates of Aboriginal children in Perth, Western Australia (WA). Methods:A purposive developed survey was distributed to 316 general practices across Perth and three key informant interviews were conducted using a mixed-methods approach.Results: Of the surveyed participants (n=101), 67.4% were unaware of the low vaccination coverage in Aboriginal children; 64.8% had not received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Inadequate awareness of community vaccination needs can contribute to barriers in vaccine service provision for Indigenous people [69]. Although Indigenous healthcare workers reported feeling insufficiently informed to be the sole HPV vaccine educators of their community, they did seek knowledge for themselves; support from the media for vaccine messaging, especially in remote communities, might alleviate some of this pressure.…”
Section: Indigenous Healthcare Worker Perspectivesmentioning
confidence: 99%
“…Inadequate awareness of community vaccination needs can contribute to barriers in vaccine service provision for Indigenous people [69]. Although Indigenous healthcare workers reported feeling insufficiently informed to be the sole HPV vaccine educators of their community, they did seek knowledge for themselves; support from the media for vaccine messaging, especially in remote communities, might alleviate some of this pressure.…”
Section: Indigenous Healthcare Worker Perspectivesmentioning
confidence: 99%
“…McBain-Rigg and Veitch [10] offer alternate reasons and suggest that ante-natal engagement is impacted by transportation issues, access affordability and cultural and language barriers. The national and international literature is consistent in terms of the perceived views held by midwives on the utility of vaccines [1,6,17]. Midwives are collectively described as being supportive of their application and use.…”
Section: Discussionmentioning
confidence: 76%
“…For Aboriginal families, it also improves the accessibility and acceptability of the available services [10,18,19]. From the provider perspective, it offers insight into past trauma and colonisation [17]. Cultural safety also provides a greater understanding of kinship and relationships in Aboriginal families, the women's responsibility to her family, and her positioning with the land, country, and environment.…”
Section: Discussionmentioning
confidence: 99%
“…The overall characteristics of included studies are summarized in each section of the key attributes of good PHC delivery [19]. Of 112 studies included, methodologically, 29 were qualitative studies [17,, 20 were cross-sectional [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71], 15 were mixed-method studies [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], 10 were national / state based surveys / census [87][88][89][90][91][92][93][94][95][96], nine were retrospective / prospective cohort [97][98]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…, in our scoping review, 36 studies[17,25,30,34,36,44,45,50,53,54,61,65,67,71,72,74,75,79,83,85,90,93,95,96,98- 102,116,122,127,128,131-133] assessed various indicators of access to PHC. Of these studies, 15 studies reported service access[36,45,53,54,71,72,74,83,85,90,99,100,102,122,132), three reported acceptability[44,65,75] and the rest of the studies assessed explanatory factors, barriers and challenges of access and coverage of PHC[17,25,30,34,50,61,67,79,93,95,96,98,101,116,127,128,131,133] (Table…”
mentioning
confidence: 99%